Penguatan Literasi dan Kepedulian Sosial Berbasis Komunitas melalui Bakti Sosial “Pendekar Pustaka” di TBM Omah Ilmu - Ach. Nizam Rifqi; Khoirul Anwar (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This community service program aims to strengthen community-based literacy and social awareness through the Pendekar Pustaka Social Service Program implemented at the Omah Ilmu Community Reading Center in Karangduren Village. The program was initiated in response to limited access to quality reading materials and low levels of reading interest and community participation in literacy activities. A participatory, community-based approach was employed, encompassing needs identification, collaborative planning, program implementation, and monitoring and evaluation. The activities included the provision of quality reading materials, children’s literacy mentoring through reading and storytelling sessions, creative educational activities, and social actions integrated with religious practices. The results indicate an increase in children’s reading interest and participation in literacy activities, enhanced social awareness among volunteers, and strengthened community involvement in managing community-based literacy initiatives. This program demonstrates that integrating literacy activities with social and religious engagement can foster an inclusive and sustainable literacy ecosystem at the community level.